Warunkowe zawieszenie wykonania kary — geneza instytucji i jej ujęcie w polskim kodeksie karnym z 1932 roku - Pasek, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
This elaboration deals with the regulation of the conditional suspension of the execution of a penalty in the Polish Penal Code of 1932. The genesis of the institution, legal provisions in force in Poland before the enactment of the Penal Code of 1932 and the rules contained in the draft prepared by the Section of the Criminal Law of the Codification Committee of the Polish Republic, based on a report prepared by Juliusz Makarewicz, were presented in the article.It has been shown that the institution of conditional suspension of the execution of a penalty in the Polish Penal Code of 1932 was formed on the basis of in-depth considerations, taking into account the achievements of European doctrine of law and legislation. During its regulation not only a popular on the European continent Franco-Belgian system, but also the indigenous experience of the validity of particular laws in the areas previously held by the former partitioning powers was used.The rules of conditional suspension of the execution of a penalty developed by Polish lawyers, constituted an important element in accordance with the demands of sociological individualization school of criminal responsibility.
Keywords: prawo karne; warunkowe zawieszenie wykonania kary; Makarewicz, Juliusz (1872-1955); Komisja Kodyfikacyjna II Rzeczypospolitej Polskiej